The Impact of MLM-STEM on Temperature and Heat Material in Students' Critical Thinking Skills - Julaila, Yuli; Sinaga, Parlindungan; Liliawati, Winny (Jurnal Pendidikan MIPA, 2023)
This study aims to measure the effectiveness of MLM-STEM on temperature and heat materials on students' critical thinking skills. The research method used in this study is a quantitative method with a quasi-experimental design. Research data were analyzed using normalized average gain, t-test, and effect size. Based on the analysis conducted, it is known that (1) the critical thinking skills in the experimental class are in the high category, while in the control class they are in the moderate category, (2) the critical thinking skills of the experimental class students using MLM-STEM are higher than the control class using electronic textbooks, (3) there is a significant difference between the improvement of critical thinking skills in the experimental class and the control class, and (4) students respond positively to the use of MLMSTEM in learning. Therefore, it can be said that MLM-STEM is a solution to improve students' critical thinking skills. Keywords: multimedia learning modules, STEM, critical thinking DOI: http://dx.doi.org/10.23960/jpmipa/v24i2.pp393-405